Marcadores inflamatórios oxidativos e hematológicos de cães com linfoma multicêntrico tratados por protocolo quimioterápico associado ou não ao óleo de cannabis - Teixeira, Bruna Antunes (2024)
Multicentric lymphoma is the most prevalent hematopoietic neoplasia in dogs, accounting for approximately 75% of canine lymphoma cases. With the growing scientific understanding of medicinal cannabis, it is now known that cannabis holds therapeutic potential for palliative treatment in cancer cases. It acts both directly and indirectly on the tumor, improving the quality of life of these patients. This study aimed to analyze the clinical staging, oxidative profile, and interleukin expression in dogs diagnosed with multicentric lymphoma, as well as evaluate the effects of combined chemotherapy treatment with the use of medicinal cannabis. The first study involved a more comprehensive analysis of dogs with a cytological diagnosis of multicentric lymphoma, without prior treatment. Oncological assessments were performed, along with the analysis of mRNA expression of interleukins 6, 10, and VEGF, as well as oxidative stress and hematological profiles. The results indicated that multicentric lymphoma is a systemic disease that disrupts the body's homeostasis, with conditions such as advanced staging, thrombocytopenia, and high VEGF expression at diagnosis potentially being associated with a less favorable prognosis. The second study reported two cases of dogs that received chemotherapy with the CHOP protocol, supplemented with broad-spectrum cannabis oil rich in 3% cannabidiol (CBD) for 60 days. The efficacy of the treatment was evaluated by assessing the reduction of adverse effects from chemotherapy, such as myelotoxicity. It was observed that the use of medicinal cannabis may have contributed to reducing side effects, particularly in modulating myelotoxicity, with variations in the intensity of neutropenia between cases. Additionally, a possible reduction in oxidative stress was noted in one of the dogs, suggesting a protective antioxidant effect of CBD. This study explored the complexity of this disease by analyzing aspects such as clinical staging, oxidative profile, and interleukin expression. Furthermore, the research highlighted the promising potential of medicinal cannabis in the palliative management of dogs with multicentric lymphoma. However, further studies are needed to consolidate these findings and establish more refined and effective treatment protocols.